2018
DOI: 10.1155/2018/1639260
|View full text |Cite
|
Sign up to set email alerts
|

Shelf Life of Extra Virgin Olive Oil and Its Prediction Models

Abstract: Extra virgin olive oil (EVOO), with high unsaturation degree (oleic acid, linoleic acid, and linolenic acid), is prone to oxidation during production and storage even with the presence of abundant antioxidants (e.g., phenolic compounds, alpha-tocopherol, and chlorophyll). The level of oxidation degradation is greatly affected by the EVOO chemical composition (free fatty acids, saturated and unsaturated fat ratio, total phenol content, etc.) and storage conditions (packaging material, oxygen, temperature, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 57 publications
(80 reference statements)
1
25
0
Order By: Relevance
“…No attempt was made to stabilize the storage conditions in the storage compartment. Although some authors recommend maintaining consistent storage parameters under non-accelerated conditions [8] this requires alternating cooling and heating and involves a substantial effort which is not a mentality trait of the common Mediterranean populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No attempt was made to stabilize the storage conditions in the storage compartment. Although some authors recommend maintaining consistent storage parameters under non-accelerated conditions [8] this requires alternating cooling and heating and involves a substantial effort which is not a mentality trait of the common Mediterranean populations.…”
Section: Resultsmentioning
confidence: 99%
“…Storage material and conditions have a significant impact on the chemical quality, organoleptic properties and shelf life (defined as the length of time under normal storage conditions within which no off-flavors or defects develop and quality parameters are within accepted limits for this commercial category) [8] of EVOO. Storage containers should not only provide protection from air, light, and humidity, but also have no chemical interaction with the oil phase which can alter oil quality and its safety aspects.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the ∼1062 cm À1 peak was newly occurred by -C-Ostretching movement. Moreover, the 3029-2989 cm À1 band was linked =CH (both -cis and -trans isomers) and -OH stretching of hydroperoxides and alcohols (Li and Wang, 2018;Tena et al, 2018). Therefore, it could be considered that the band over 2952 cm À1 and ∼1062 cm À1 peaks were a fingerprint of the slow-paced autoxidation process.…”
Section: Determination Of Ftir Spectramentioning
confidence: 99%
“…Therefore, it could be considered that the band over 2952 cm À1 and ∼1062 cm À1 peaks were a fingerprint of the slow-paced autoxidation process. Silverstein et al, 1981;Guillèn and Cabo, 2000;Maggio et al, 2009;Jiang et al, 2016;Li and Wang, 2018;Tena et al, 2018. A previous study demonstrated that 1744 cm À1 (C=O stretching vibration of aldehydes and ketones), 2922 cm À1 (CH 2 asymmetric stretching) and 3006 cm À1 (OH stretching of hydroperoxides) bands could be used for differentiating VOOs in terms of chemical bond vibrational mode. 1463 cm À1 (scissoring mode of -CH in CH 2 ), 1160 cm À1 (stretching of C-O and bending of -CH 2 ), 1118 cm À1 (stretching of C-O), 1096 cm À1 (stretching of C-O) and 723 cm À1 (rocking mode of -(CH 2 ) n and out-of-plane bending mode of cis -HC=CH) bands showed similar loadings at PCA due to the intensity of the functional group (Li and Wang, 2018).…”
Section: Determination Of Ftir Spectramentioning
confidence: 99%
“…[6,13]. The decrease in antioxidant levels as a result of the refining process is relevant because oxidative stability is not only a quality parameter but also represents one of the most important oil indicators of shelf-life [14]. During oxidation, compounds responsible for unpleasant odors are produced, thus making the oil less acceptable or unacceptable for the consumer or for the industries that use it as an ingredient.…”
Section: Introductionmentioning
confidence: 99%